Characteristics of community seed schemes for grains and legumes: Insights from northern Nigeria - Takeshima, Hiroyuki; Ragasa, Catherine; Bamiwuye, Temilolu; Fasoranti, Adetunji; Omoigui, Lucky (International Food Policy Research Institute, 2024)
CONTEXT: Despite the significant roles that intermediary seed systems play in the supply of quality seeds in developing countries, including Africa south of the Sahara, the knowledge gap remains generally substantial regarding the general characteristics and seed quality control performance of intermediary seed systems such as community seed schemes (CSS), which still operate predominantly outside the formal seed systems.